'FARÒ IL POSSIBILE PER VINCER L'ANIMO DI M.R HANDEL': SENESINO'S ARRIVAL IN LONDON AND ARSACE'S RHETORIC OF PASSIONS. (16th February 2017) - BUCCIARELLI, MELANIA
ABSTRACT: We often read about the castrato Senesino's arrogant, self-absorbed personality, especially in relation to Handel and his London years. Concerns about Senesino's difficult character spread in London even before his arrival in September 1720. That this preoccupied the singer is shown in his correspondence with Giuseppe Riva, which reveals that Senesino was also apprehensive about working with the composer. Evidence shows that Senesino sought to control his debut through the choice of and involvement in a production of the opera Arsace . The selection of a libretto that exploits a subject drawn from British history, the poetic and dramaturgical revisions made by Rolli to the original text from 1715, and the changes and additions to Orlandini's original score all brought Senesino to the fore. That Senesino's voice stood as a strong argument in his rhetorical strategy may not be surprising; the aria type that he chose and the avoidance of ostentatious ornamentation are unexpected, however, and may reveal a more subtle plan of self-fashioning.